Auditoría de gestión al Gobierno Autónomo Descentralizado Parroquial de Vilcabamba, del 1 de enero al 31 de diciembre del 2015 - Domínguez Herrera, Raquel Alexandra (2017)
The title work: Management Audit to the Parochial Decentralized Autonomous Government of Vilcabamba from January 1 to December 31, 2015, was carried out with the purpose of efficiently improving the operations carried out in the institution. Specific objectives were set out for its development, such as: evaluating the internal control structure, which was applied to the internal control questionnaire, which helped to know the level of risk and the level of confidence of each area examined; The second objective was aimed at measuring the degree of compliance with current legal and regulatory provisions, for which purpose the narrative, analytical, and application of indicators were drawn up, which were based on legal regulations; The third objective was to draft the management audit report, which was carried out based on the results of the management audit carried out at Vilcabamba Parish GAD, which contains comments, conclusions and recommendations that will allow it to improve the deficiencies found. Finally, the conclusion of the results of the management audit in the Vilcabamba Autonomous Decentralized Government is detailed, where it is denoted that it does not have the annual operational plan (POA), which should contain the goals and indicators according to the needs of the Parish and community to facilitate the evaluation of each activity carried out so it is recommended to the president to elaborate the annual operational plan with the relevant institutions.